2022
DOI: 10.1007/s40042-022-00442-w
|View full text |Cite
|
Sign up to set email alerts
|

Plasma bioscience for medicine, agriculture and hygiene applications

Abstract: Nonthermal biocompatible plasma (NBP) sources operating in atmospheric pressure environments and their characteristics can be used for plasma bioscience, medicine, and hygiene applications, especially for COVID-19 and citizen. This review surveyed the various NBP sources, including a plasma jet, micro-DBD (dielectric barrier discharge) and nanosecond discharged plasma. The electron temperatures and the plasma densities, which are produced using dielectric barrier discharged electrode systems, can be characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 187 publications
(312 reference statements)
0
24
0
Order By: Relevance
“…In the last decade, it has been demonstrated that the RONS deposited into liquids can have antitumor/cancer, antibacterial and antimicrobial effect, and can induce oxidative stress to cells. An overview of the demonstrating studies has been given in Ref., [ 1,2 ] which indicate that the main role is played by the long‐lived RONS either directly or indirectly. The disinfecting property of PAL has been attributed to the synergistic effect of different RONS, [ 3,4 ] while in several studies, the emphasize is given to the pH of the solution or/and the peroxynitrite, peroxynitrous acid (ONOOH) and peroxynitric acid (O2 ${{\rm{O}}}_{2}$NOOH), which are created from the reaction of H2O2 ${{\rm{H}}}_{2}{{\rm{O}}}_{2}$ with NO2 ${\text{NO}}_{2}^{-}$ under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, it has been demonstrated that the RONS deposited into liquids can have antitumor/cancer, antibacterial and antimicrobial effect, and can induce oxidative stress to cells. An overview of the demonstrating studies has been given in Ref., [ 1,2 ] which indicate that the main role is played by the long‐lived RONS either directly or indirectly. The disinfecting property of PAL has been attributed to the synergistic effect of different RONS, [ 3,4 ] while in several studies, the emphasize is given to the pH of the solution or/and the peroxynitrite, peroxynitrous acid (ONOOH) and peroxynitric acid (O2 ${{\rm{O}}}_{2}$NOOH), which are created from the reaction of H2O2 ${{\rm{H}}}_{2}{{\rm{O}}}_{2}$ with NO2 ${\text{NO}}_{2}^{-}$ under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, OH (A 2 ∑ + → X 2 Π) radicals is prominently seen at 309 nm [27] in the spectrum of the gliding arc discharge which plays a crucial role in plasma chemical reactions such as the oxidation of gas and liquid pollutants [28]. The nitric oxide gamma band NO γ (A 2 ∑ + → X 2 Π) is observed in 200 to 280 nm [28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…RONS are considered to play a major role in the application of PAW in agriculture, medical, and food, and in biological sciences [31]. As shown in figure 4(a), the concentration of H 2 O 2 in PAW was decreased significantly (P < 0.05) as storage time was extended.…”
Section: Rons Concentration In Pawmentioning
confidence: 99%
“…This may be due to the fact that the short-lived active substance in PAW is not completely dissipated in a short period of time, while prolonged treatment causes persistent damage to the bacterial cell structure and reduces the presence of sublethal bacteria. It was reported that low-temperature storage is conducive to the disinfection ability of PAW, but storage for a long time will weaken it, because more active substances are dissipated during storage [31,34].…”
Section: Rons Concentration In Pawmentioning
confidence: 99%